Measured and Predicted Turbulent Kinetic Energy in Flow Through Emergent Vegetation With Real Plant Morphology. Issue 12 (24th November 2020) - Xu, Yuan; Nepf, Heidi
Abstract: Velocity and forces on individual plants were measured within an emergent canopy with real plant morphology and used to develop predictions for the vertical profiles of velocity and turbulent kinetic energy ( TKE ). Two common plant species, Typha latifolia and Rotala indica, with distinctive morphology, were considered. Typha has leaves bundled at the base, and Rotala has leaves distributed over the length of the central stem. Compared to conditions with a bare bed and the same velocity, the TKE within both canopies was enhanced. For the Typha canopy, for which the frontal area increased with distance from the bed, the velocity, integral length‐scale, and TKE all decreased with distance from the bed. For the Rotala, which had a vertically uniform distribution of biomass, the velocity, integral length‐scale, and TKE were also vertically uniform. A turbulence model previously developed for random arrays of rigid cylinders was modified to predict both the vertical distribution and the channel‐average of TKE by defining the relationship between the integral length‐scale and plant morphology. The velocity profile can also be predicted from the plant morphology. Combining with the new turbulence model, the TKE profile was predicted from the channel‐average velocity and plant frontal area. Key Points: Within an emergent canopy, vertical profiles of velocity and TKE vary inversely with the vertical distribution of plant frontal area A turbulence model for cylinders was modified to predict the vertical‐distribution and the channel‐average of TKE TKE profiles can be predicted from the channel‐average velocity and the vertical distribution of plant frontal area